2005
DOI: 10.1111/j.1365-2966.2005.09030.x
|View full text |Cite
|
Sign up to set email alerts
|

Foreground contributions to the cosmic microwave background

Abstract: A detailed search has been made for evidence of residual foreground contributions to the cosmic microwave background (CMB) in the map generated by the Wilkinson Microwave Anisotropy Probe (WMAP), a map that has been (nominally) cleaned for the foreground already. We find positive results in that various features relate to Galactic properties. For example, on the largest angular scales we find significant differences between the power in the fluctuations for positive and negative Galactic latitudes and between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…In our recent publication ( [10]), which confirmed results reported by us about ten years ago ( [9]) with the one-year only WMAP data, Tegmark, de Oliviera-Costa & Hamilton [8], we have shown that there is strong evidence that the procedure of eliminating the known and identified foreground contributions is not perfect. We have found some contributions from large Galactic structures which have not been taken into account yet.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our recent publication ( [10]), which confirmed results reported by us about ten years ago ( [9]) with the one-year only WMAP data, Tegmark, de Oliviera-Costa & Hamilton [8], we have shown that there is strong evidence that the procedure of eliminating the known and identified foreground contributions is not perfect. We have found some contributions from large Galactic structures which have not been taken into account yet.…”
Section: Introductionsupporting
confidence: 87%
“…We supposed that the EGRET map (with point sources excluded) is a view of the possible foreground on CMB maps caused by the cosmic rays and Galactic matter structures. The correlation between the EGRET gamma ray flux and the temperature fluctuations measured in this direction by WMAP was used in our previous papers [9,10]. We have followed this way of constructing the sky map of the respective correlation coefficients for the polarization parameters of WMAP.…”
Section: The Analysismentioning
confidence: 99%
“…• , l = 237 • ) (Bunn & Scott 2000;Copi et al 2004;Eriksen et al 2004a;Hansen et al 2004a,b;Wibig 2005;Land & Magueijo 2005a,b;Schwarz et al 2004;Prunet et al 2005;Donoghue & Donoghue 2005), as well as indications 1 Throughout this paper we use galactic coordinates with origin at b = 90…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a correlation is found (Wibig and Wolfendale 2005) between the CMB (Hinshaw et al 2006) temperature and gamma ray intensities (Cillis and Hartman 2005) and other cosmic ray indicators. For example, regions of the Galaxy having (line of sight) steep cosmic ray energy spectra have low mean CMB temperatures and the important Loop I edge region, where the cosmic ray intensity is high, has a high mean temperature.…”
Section: Correlation Of Cosmic Rays (Egret γ -Rays) Andmentioning
confidence: 95%